Economic and Financial Impact of the COVID-19 Pandemic on Private Dental Clinics in Yaoundé Cameroon - Njoumemi, Zakariaou; Mekontso, Suzie Laurence Kognoujui; Ndjoh, Julien; Kamgno, Joseph (British Journal of Healthcare and Medical Research, 2025)
Background: The COVID-19 pandemic has had significant economic and financial repercussions on private dental clinics worldwide, particularly in low-income African countries where few studies have been conducted on the subject. Objective: To assess the economic and financial impact on private dental clinics in the city of Yaoundé before, during, and after the COVID-19 pandemic. Methods: A descriptive, retrospective cross-sectional study was conducted in 20 private dental clinics in the city of Yaoundé. Data were collected and analyzed using SPSS version 26.0 and Microsoft Excel 2016. Results were presented as frequencies, percentages, and means in tables and graphs. Fisher’s exact test was used at a fixed significance level of 5%. Results: The study sampled 20 private dental clinics. While the average annual volume of services dropped substantially in 2020 by 43.7% and 40.9% in comparison of 2018 and 2019 respectively, they slightly improved from 2021. The average annual revenues dropped by 50.4% and 45.3% as compared to the years 2018 and 2019 respectively. The overall financial revenues were lower in 2020 representing 15.8% of cumulative overall total five years’ total revenues compared to 21.5% in 2018 and 20.5% in 2019, while the financial revenues increase to 19.7% in 2021 and 22.5% in 2022. Conclusion: The economic and financial impacts were mainly due to declines in business volume, reduced revenue due to lower attendance, the need for new investments, and adaptation strategies to address the COVID-19 pandemic crisis. Public authorities should provide financial support to dental practices during health crises.